Self-supporting membrane for negative electrode of lithium
By using triblock copolymers containing soft blocks and hard blocks as binders, the problem of poor cycling stability of the negative electrode of the lithium secondary battery under negative potential is solved, and higher tensile strength and stability are achieved. Reduced manufacturing costs.
Patent Information
- Application Number
- CN202311665935.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-14
- Filing Date
- 2023-12-06
- Publication Date
- 2025-02-21
AI Technical Summary
When polytetrafluoroethylene (PTFE) used in the prior art is used as a binder to manufacture the negative electrode of a lithium secondary battery, there is a problem of poor cycle stability, especially in a negative potential environment.
A triblock copolymer containing soft and hard blocks is used as a binder to form excellent mechanical properties and stable self-supporting films through strong interaction with the negative electrode active material and the conductive material.
A binder that is stable even under a negative potential is realized, the cycle stability and tensile strength of the negative electrode of the lithium secondary battery are improved, and the manufacturing cost is reduced.
Smart Images

Figure CN119495702A_ABST
Abstract
Description
[0001] Related Applications
[0002] This application claims the benefit of priority from Korean Patent Application No. 10-2023-0106485 filed on August 14, 2023, in the Korean Intellectual Property Office, the entire contents of which are incorporated herein by reference. Technical Field
[0003] The present disclosure relates to a method for manufacturing a self-supporting film for a negative electrode of a lithium secondary battery using a binder including a triblock copolymer containing a soft block and a hard block, and the self-supporting film for a negative electrode of a lithium secondary battery manufactured using the method. Background Art
[0004] Since its first commercialization in the 1990s, lithium secondary batteries have been widely used in the portable electronic device market and continue to receive attention as the most widely studied energy storage system. Due to the characteristics of lithium secondary batteries such as high operating voltage, high energy density, low self-discharge rate, high rate performance, and long cycle stability, lithium secondary batteries meet the appropriate requirements as an energy source for electric vehicles.
[0005] However, lithium secondary batteries used in electric vehicles face three major problems: safety, operating time, and cost. The problems of safety and operating time can be solved by all-solid-state batteries, but cost becomes a factor that prevents the widespread use of lithium secondary batteries. Therefore, in order to reduce the cost of lithium secondary batteries, a lot of research has been conducted.
[0006] Reducing the energy consumption required to manufacture lithium secondary batteries or increasing the thickness of electrodes is one of the most effective ways to reduce the manufacturing cost of lithium secondary batteries. Conventional electrode manufacturing technology forms electrodes by casting a slurry in which an electrode active material, a polymer binder and a conductive additive are mixed with each other in water or an organic solvent onto a collector, and drying and pressing the cast slurry. The energy required to prepare the slurry and apply the slurry to the collector accounts for about 50% of the energy consumed in the entire manufacturing process. In order to reduce the manufacturing cost of lithium secondary batteries, methods for manufacturing electrodes in a dry manner without solvents have been studied.
[0007] To this, the scheme of the positive pole of lithium secondary battery manufactured by dry method of polytetrafluoroethylene (PTFE) with excellent adhesiveness is proposed. However, PTFE has low LUMO (lowest unoccupied molecular orbital) energy level, so it can easily accept electrons, and is therefore electrochemically unstable under negative potential environment. The carbon yne produced by PTFE accepting electrons can not withstand the volume expansion and contraction in charge and discharge treatment. Therefore, the negative pole of the lithium secondary battery manufactured using PTFE as a binder has the problem of poor cycle stability.
[0008] Therefore, there is a need to develop a scheme for manufacturing a negative electrode in a dry manner using a binder that is stable even at negative potential. Summary of the invention
[0009] The present disclosure is directed to solving the above-mentioned problems occurring in the prior art while keeping the advantages achieved by the prior art intact.
[0010] In one aspect, a method for manufacturing a self-supporting film suitable for a negative electrode of a lithium secondary battery is provided, the method comprising: a) forming a first electrode active membrane material using a composition comprising i) a negative electrode active material, ii) a conductive material, and iii) a binder; b) processing the first electrode active material to obtain a composite powder; and c) forming a second electrode active membrane material using the composite powder, wherein iii) the binder comprises a triblock copolymer, the triblock copolymer comprising: a) a soft block derived from an aliphatic or alicyclic diene monomer and having a rubber phase at room temperature; and b) a first hard block and a second hard block, which are respectively connected to both ends of the soft block and are derived from an ethylenically unsaturated monomer containing an aromatic ring and have a glass phase at room temperature.
[0011] One aspect of the present disclosure provides a self-supporting film for a negative electrode of a lithium secondary battery, the self-supporting film is manufactured using a binder, the binder includes a triblock copolymer containing a hard block and a flexible soft block that contribute to excellent mechanical properties. The binder is firmly combined with the negative electrode active material, and has good formability, and is stable even at a negative potential level, and has excellent tensile strength, and is strongly combined with the negative electrode active material and the conductive material to form a three-dimensional network, and one aspect of the present disclosure provides a method for manufacturing the same, and provides a negative electrode for a lithium secondary battery including a self-supporting film, and provides a lithium secondary battery including a negative electrode.
[0012] The technical problems to be solved by the present disclosure are not limited to the above-mentioned problems, and any other technical problems not mentioned herein will be clearly understood by those skilled in the art to which the present disclosure belongs from the following description.
[0013] According to one aspect of the present disclosure, a method for manufacturing a self-supporting film for a negative electrode of a lithium secondary battery includes: performing a first film forming process using a composition for forming a negative electrode of a lithium secondary battery to obtain a first negative electrode active material layer, wherein the composition includes a negative electrode active material, a conductive material, and a binder; processing the first negative electrode active material layer to obtain a composite powder for forming a negative electrode as a pulverized product; and performing a second film forming process using the composite powder to obtain a second negative electrode active material layer, wherein the binder includes a triblock copolymer, the triblock copolymer having: a soft block derived from an aliphatic or alicyclic diene monomer and having a rubber phase at room temperature; and a first hard block and a second hard block respectively connected to both ends of the soft block and derived from an aromatic ring-containing ethylenically unsaturated monomer and having a glass phase at room temperature.
[0014] In one aspect, the composite powders disclosed herein may include powder elements each having an elliptical shape, and an average sphericity thereof in the range of 0.6 to 0.8. In certain aspects, these composite powders include powder elements each having an average diameter (D) in the range of 100 μm to 300 μm. 50 ) particles.
[0015] In one aspect, the binder includes particles having a spherical shape, and the average sphericity thereof is in the range of 0.8 to 1.0.
[0016] In one aspect, the binder of the self-supporting film composition suitably comprises two or more particles each having an average diameter (D 50 ) particles.
[0017] In one aspect, in the self-supporting film composition, suitably, the first glass transition temperature and the second glass transition temperature corresponding to the first hard block and the second hard block, respectively, are each in the range of 50°C to 120°C, wherein the third glass transition temperature corresponding to the soft block is in the range of -120°C to -50°C.
[0018] In one aspect, in the self-supporting film composition, suitably, the soft block is derived from an aliphatic or alicyclic diene-based monomer, which includes at least one selected from the group consisting of a butadiene-based monomer, a pentadiene-based monomer, and a hexadiene-based monomer.
[0019] In one aspect, in the self-supporting film composition, suitably, the first hard block and the second hard block are each independently derived from an aromatic ring-containing ethylenically unsaturated monomer comprising at least one of a styrenic monomer and an aromatic (meth)acrylic monomer.
[0020] In one aspect, in the self-supporting film composition, suitably, at least one of 1) forming the first electrode active membrane material and 2) forming the second electrode active membrane material comprises calendaring, wherein the calendaring is performed at a temperature equal to or higher than the first glass transition temperature and the second glass transition temperature corresponding to the first hard block and the second hard block, respectively.
[0021] In one aspect, a negative electrode for a lithium secondary battery comprising a composition as described herein is provided.
[0022] In one aspect, there is provided a lithium secondary battery comprising a negative electrode as described herein.
[0023] In one aspect, there is provided a vehicle comprising a lithium secondary battery as described herein.
[0024] As referred to herein, the rubber phase or state is above the T of the material. g (glass transition temperature), i.e., where the material can be in a rubberier state and be relatively soft and flexible. Thus, when it is stated herein that a material forms a rubber phase at room temperature (e.g., 25°C), the material can be above its glass transition temperature at room temperature (25°C) and can be in a relatively rubberier or more flexible state.
[0025] As referred to herein, the glassy phase or state is below the T of the material. g (glass transition temperature), and wherein the material may be in a more rigid or glassy configuration. Thus, when it is stated herein that a material forms a glass phase at room temperature (e.g., 25° C.), the material may be below its glass transition temperature at room temperature (25° C.) and may be in a relatively rigid or hardened state.
[0026] The term "all-solid-state battery" as used herein refers to a rechargeable secondary battery including a solid electrolyte (e.g., a gel or polymer (cured)), which may include ionomers and other electrolytic components for transferring ions between the electrodes of the battery. In some aspects, the lithium secondary battery referred to herein is an all-solid-state battery.
[0027] The term "self-supporting" as used herein includes that the film can take the form of a sheet and can be handled as an independent sheet without the aid of a substrate or support. Therefore, the term "self-supporting" can have the same meaning as "self-supporting".
[0028] As referred to herein, the term "block polymer" includes polymers comprising two or more chemically distinct regions or segments (referred to as "blocks") that are typically linked in a linear manner, e.g., a polymer comprising chemically distinct units linked end to end (covalently bonded) with respect to polymerized functionality, rather than in a pendant or grafted manner. In one aspect, a block polymer may include (i) a first polymer block comprising at least 5, 10, 20, or 30 first repeating units; and (ii) a second polymer block comprising at least 5, 10, 20, or 30 second repeating units.
[0029] As referred to herein, the terms "soft block" and "hard block" indicate that the structure and one or more characteristics of each polymer unit or portion are, for example, different. In some aspects, the soft block can have a lower glass transition temperature or melting temperature (e.g., below room temperature) than the hard block (which can have a higher glass transition temperature or melting temperature, for example, above room temperature), and the glass transition temperature or melting temperature of the hard block can be higher than the application temperature of the formed block copolymer material. In some embodiments, the T of the hard block and the soft block are different. g The difference may be, for example, up to or exceeding, for example, 3°C, 5°C, 10°C, 20°C or 30°C.
[0030] According to another aspect of the present disclosure, a self-supporting film for a negative electrode of a lithium secondary battery includes: a negative electrode active material layer, the negative electrode active material layer includes multiple domains of negative electrode active material, multiple domains of conductive material and a binder, wherein the binder contains a triblock copolymer, the triblock copolymer having: a soft block derived from an aliphatic or alicyclic diene monomer and having a rubber phase at room temperature; and a first hard block and a second hard block respectively connected to both ends of the soft block, the first hard block and the second hard block being derived from an aromatic ring-containing ethylenically unsaturated monomer and having a glass phase at room temperature, wherein the binder has a discontinuous pillar connecting one domain of active material or one domain of conductive material to another domain of active material or another domain of conductive material, wherein the binder has an average width perpendicular to the length direction of the binder in the range of 10 nm (inclusive) to 150 nm (inclusive).
[0031] According to yet another aspect of the present disclosure, a negative electrode for a lithium secondary battery includes: a current collector; and a self-supporting film for a negative electrode for a lithium secondary battery disposed on the current collector, wherein the self-supporting film includes the self-supporting film for a negative electrode for a lithium secondary battery as defined above.
[0032] According to still another aspect of the present disclosure, a lithium secondary battery includes: a negative electrode for a lithium secondary battery; a positive electrode for a lithium secondary battery; and an electrolyte.
[0033] Other aspects of the invention are disclosed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The above and other objects, features and advantages of the present disclosure will become more apparent from the following detailed description in conjunction with the accompanying drawings:
[0035] Figure 1 is a schematic diagram showing the internal structure of a binder included in a self-supporting film for a negative electrode of a lithium secondary battery according to one embodiment of the present disclosure;
[0036] Figure 2A is a schematic diagram of a method for manufacturing a self-supporting film for a negative electrode of a lithium secondary battery according to one embodiment of the present disclosure;
[0037] Figure 2B is a diagram schematically illustrating a binder change mechanism during a manufacturing process of a self-supporting film for a negative electrode of a lithium secondary battery according to an embodiment of the present disclosure;
[0038] Figure 3A and Figure 3B shows an SEM image of a mixed powder formed after pulverization in the manufacturing process of a self-supporting film for a negative electrode of a lithium secondary battery according to the present Example 1;
[0039] Figure 3C shows the results of particle size analysis of mixed powder particles formed after pulverization in the process of manufacturing the self-supporting film for the negative electrode of the lithium secondary battery according to the present Example 1;
[0040] FIG. 4A to FIG. 4C A SEM image of a self-supporting film for a negative electrode of a lithium secondary battery according to Example 1 is shown;
[0041] FIG. 4D to FIG. 4F shows a SEM image of a self-supporting film for a negative electrode of a lithium secondary battery according to Reference Example 1;
[0042] Figure 4G Schematically shows a network structure composed of a binder and a negative electrode active material or a conductive material in a self-supporting film for a negative electrode of a lithium secondary battery;
[0043] Figure 5A shows the results of an experiment to evaluate the electrolyte stability of this Example 1;
[0044] Figure 5B shows the results of an experiment to evaluate the stability of the electrolyte of Reference Example 1;
[0045] Fig. 6A Evaluation results of the tensile strength of the self-supporting films for a negative electrode according to Examples 1 to 3 and Reference Example 1 are shown.
[0046] Figure 6B and Figure 6C shows a flexibility evaluation experiment of the self-supporting film for a negative electrode according to the present Example 1; and
[0047] Figure 7 The performance evaluation results of the lithium secondary battery according to each of the present Example 4 and Reference Example 4 are shown. DETAILED DESCRIPTION
[0048] From the following preferred embodiments associated with the accompanying drawings, it will be easy to understand the above-mentioned goals, other goals, features and advantages of the present disclosure. However, the present disclosure is not limited to the embodiments described herein and can be embodied in other forms. The embodiments described herein are provided so that the present disclosure can be thorough and complete, and the spirit of the present disclosure can be fully conveyed to those skilled in the art. Throughout the accompanying drawings, the same elements are represented by the same reference numerals. In the accompanying drawings, for the clarity of the present disclosure, the size of the structure is larger than the actual size. The terms "first", "second" and the like used in this specification can be used to describe various components, but the components should not be interpreted as being limited to these terms. These terms are only used for the purpose of distinguishing a component from another component. For example, without departing from the scope of the present disclosure, the first component can be referred to as the second component, and the second component can also be referred to as the first component. As used herein, unless the context clearly indicates otherwise, the singular forms "one", "an" and "the" are intended to also include plural forms. It will be further understood that when the terms "comprises", "comprising" or "having" are used in this specification, they specify the presence of the stated features, regions, wholes, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, regions, wholes, steps, operations, elements, parts and / or combinations thereof. It should also be understood that when an element such as a layer, film, region or sheet is referred to as "on" another element, it can be directly on another element, or there can be an intermediate element therebetween. Similarly, when an element such as a layer, film, region or sheet is referred to as "below" another element, it can be directly below another element, or there can be an intermediate element therebetween. Unless otherwise specified, all numerical values, values, and / or representations used in this article to represent the amount of components, reaction conditions, polymer compositions, and mixtures should be considered approximate values, including various uncertainties that affect measurement, which inherently occur in obtaining these values, etc., and are therefore understood to be modified by the term "about" in all cases. Unless otherwise specified or apparent from the context, as used herein, the term "about" should be understood to be within the normal tolerance range in the art, such as within 2 standard deviations of the mean. "About" can be understood to be within 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.1%, 0.05% or 0.01% of the value. Unless otherwise clear from the context, all numerical values provided herein are modified by the term "about".
[0049] In addition, when a numerical range is disclosed in this specification, the range is continuous and includes all values from the minimum value of the range to its maximum value, unless otherwise specified. In addition, when such a range involves an integer value, all integers from the minimum value to the maximum value are included, unless otherwise specified. For example, a range of "5 to 10" should be understood to include any subranges, such as 6 to 10, 7 to 10, 6 to 9, 7 to 9, etc., as well as individual values of 5, 6, 7, 8, 9 and 10, and should also be understood to include any value between the valid integers in the range, such as 5.5, 6.5, 7.5, 5.5 to 8.5, 6.5 to 9, etc. In addition, for example, a range of "10% to 30%" will be understood to include sub-ranges such as 10% to 15%, 12% to 18%, 20% to 30%, etc., and all integers, including values of 10%, 11%, 12%, 13%, etc. up to 30%, and will also be understood to include any values between the significant integers in the stated range, such as 10.5%, 15.5%, 25.5%, etc.
[0050] It should be understood that the term "vehicle" or "vehicle-like" or other similar terms as used herein include a broad range of motor vehicles, such as passenger cars, including sports utility vehicles (SUVs), buses, trucks, various commercial vehicles, ships (including various ships and boats), aircraft, etc., and include hybrid vehicles, electric vehicles, plug-in hybrid electric vehicles, hydrogen-powered vehicles and other alternative fuel vehicles (e.g., SUVs. Fuels derived from resources other than petroleum). As mentioned herein, a hybrid vehicle is a vehicle with two or more power sources, for example, gasoline-powered and electric vehicles. In certain preferred aspects, the vehicle can be electric, including a hybrid vehicle, a plug-in hybrid vehicle, or a vehicle in which electricity is the main or only power source.
[0051] Hereinafter, a method for manufacturing a self-supporting film for a negative electrode of a lithium secondary battery and a self-supporting film for a negative electrode of a lithium secondary battery manufactured using the method will be described in detail so that those skilled in the art can easily implement the method and the self-supporting film.
[0052] According to one embodiment of the present disclosure, a method for manufacturing a self-supporting film for a negative electrode of a lithium secondary battery includes performing a first film forming process using a composition for forming a negative electrode of a lithium secondary battery to obtain a first negative electrode active material layer, wherein the composition includes a negative electrode active material, a conductive material, and a binder; processing, for example, by pulverizing the first negative electrode active material layer to obtain a composite powder for forming a negative electrode as a pulverized product; and performing a second film forming process using the composite powder to obtain a second negative electrode active material layer, wherein the binder comprises a triblock copolymer, the triblock copolymer having: a soft block derived from an aliphatic or alicyclic diene monomer and having a rubber phase at room temperature; and a first hard block and a second hard block respectively connected to both ends of the soft block, the first hard block and the second hard block being derived from an ethylenically unsaturated monomer containing an aromatic ring and having a glass phase at room temperature.
[0053] The binder included in the composition for forming the negative electrode before the first film forming process may be substantially spherical and may have a spherical or substantially spherical shape, and specifically, its average sphericity may be in the range of 0.7 to 1.0, preferably 0.8 to 1.0, and more preferably 0.9 to 1.0. That is, each binder particle in the composition for forming the negative electrode of the lithium secondary battery before the first film forming process may maintain a substantially spherical shape and may be dispersed in the composition for forming the negative electrode.
[0054] In this regard, the sphericity of the binder can be derived as follows: the maximum diameter and the minimum diameter of 10 randomly selected particles can be measured using an image of the binder particles observed with a scanning electron microscope (SEM), and the ratio of the minimum diameter / maximum diameter of each particle can be obtained, and then the average value of the ratio of the minimum diameter to the maximum diameter can be defined as the sphericity. When the sphericity is closer to 1, the shape of the particle can be closer to a sphere.
[0055] The binder may include particles each having an average diameter (D 50 ) particles.
[0056] In this regard, the average diameter of the binder (D 50 ) refers to the diameter corresponding to the cumulative 50% of the cumulative volume distribution measured by a laser diffraction / scattering particle size distribution measuring device.
[0057] The soft block may include repeating units derived from aliphatic diene monomers and / or alicyclic diene monomers and have a rubber phase at room temperature. Specifically, the soft block may be derived from aliphatic or alicyclic diene monomers, including at least one selected from the group consisting of butadiene monomers, pentadiene monomers, and hexadiene monomers.
[0058] The butadiene-based monomer may include at least one selected from the group consisting of 1,2-butadiene, 1,3-butadiene, isoprene, and chloroprene.
[0059] The pentadiene monomer may include at least one selected from the group consisting of 1,2-pentadiene, 1,3-pentadiene, 1,4-pentadiene, 2,3-pentadiene, 2-methyl-1,3-pentadiene, 2-methyl-1,4-pentadiene, 2-methyl-2,3-pentadiene, 2-methyl-2,4-pentadiene, 3-methyl-1,3-pentadiene, 3-methyl-1,4-pentadiene, 4-methyl-1,3-pentadiene, 2-ethyl-1,3-pentadiene, 2-ethyl-1,4-pentadiene, 2-ethyl-2,4-pentadiene, 3-ethyl-1,3-pentadiene, 3-ethyl-1,4-pentadiene, 4-ethyl-1,3-pentadiene, 1-chloro-1,3-pentadiene, 1-chloro-2,4-pentadiene, 2-chloro-1,3-pentadiene, 3-chloro-1,3-pentadiene, 3-chloro-1,4-pentadiene and 5-chloro-1,3-pentadiene.
[0060] The hexadiene monomer may include at least one selected from the group consisting of 1,2-hexadiene, 1,3-hexadiene, 1,4-hexadiene, 1,5-hexadiene, 2,3-hexadiene, 2,4-hexadiene, 2,5-hexadiene, 3,5-hexadiene, 2-methyl-1,3-hexadiene, 2-methyl-1,4-hexadiene, 2-methyl-1,5-hexadiene, 2-methyl-2,3-hexadiene, 2-methyl-2,4-hexadiene, 3-methyl-1,2-hexadiene, 3-methyl-1,3-hexadiene, 3-methyl-1, 4-hexadiene, 3-methyl-1,5-hexadiene, 3-methyl-2,4-hexadiene, 3-methyl-2,5-hexadiene, 4-methyl-1,3-hexadiene, 4-methyl-1,4-hexadiene, 4-methyl-2,3-hexadiene, 5-methyl-1,3-hexadiene, 5-methyl-1,4-hexadiene, 2-ethyl-1,3-hexadiene, 2-ethyl-1,4-hexadiene, 3-ethyl-1,2-hexadiene, 3-ethyl-1,3-hexadiene, 3-ethyl-1,4-hexadiene and 3-ethyl-1,5-hexadiene.
[0061] The triblock copolymers containing the soft blocks have excellent properties of flexibility, extrudability and wear resistance.
[0062] The first and second hard blocks may include repeating units derived from an ethylenically (olefinically) unsaturated monomer containing an aromatic ring and have a glass phase at room temperature. Specifically, the aromatic ring contained in the ethylenically unsaturated monomer may be a substituted or unsubstituted benzene ring or a substituted or unsubstituted naphthalene ring.
[0063] Furthermore, the aromatic ring may be linked to a main chain or a side chain of a repeating unit of each of the first hard block and the second hard block, and may preferably be linked to a side chain of a repeating unit of each of the first hard block and the second hard block.
[0064] Each of the first hard block and the second hard block may be independently derived from an aromatic ring-containing ethylenically unsaturated monomer including at least one of a styrenic monomer and an aromatic (meth)acrylic monomer.
[0065] The styrene-based monomer may include at least one selected from the group consisting of styrene, α-methylstyrene, p-methylstyrene, p-methoxystyrene, p-ethoxystyrene, tert-butoxystyrene, p-acetoxystyrene, p-chlorostyrene, p-bromostyrene, 2,4-dimethylstyrene, 3,5-dimethylstyrene and 2,4,6-trimethylstyrene.
[0066] The aromatic (meth)acrylic monomer may include at least one selected from the group consisting of benzyl acrylate, benzyl methacrylate, phenoxy acrylate, phenoxy methacrylate, phenyl acrylate, phenyl methacrylate, phenethyl acrylate, and phenethyl methacrylate.
[0067] Each of the first hard block and the second hard block can be strongly bound to the negative electrode active material or the conductive material by the π-π interaction due to the aromatic ring structure contained in its repeating unit. In addition, each of the first hard block and the second hard block can form a crosslink due to a physical bond with a relatively low binding energy, and thus can maintain its shape and size at a temperature below the glass transition temperature, while being easily formed at a temperature above the glass transition temperature. Therefore, when a self-supporting film for a negative electrode is manufactured at a temperature at which a triblock copolymer can be formed, the triblock copolymer can be flexibly deformed while each of the hard blocks contained in the triblock copolymer remains bound to the negative electrode active material or the conductive material. Therefore, the binding portion can provide a physical crosslinking point in a linear form (in the form of a discontinuous column or line), so that a solid three-dimensional network structure can be formed around the point.
[0068] Furthermore, the first hard block and the second hard block can impart high strength characteristics to the triblock copolymer containing them.
[0069] Specifically, the self-supporting film for the negative electrode of a lithium secondary battery according to one embodiment of the present disclosure can be performed by using a composition for forming a negative electrode of a lithium secondary battery to perform a first film forming process to obtain a first negative electrode active material layer; treating (e.g., pulverizing) the first negative electrode active material layer to obtain a composite powder as a treated product; and performing a second film forming process using the composite powder to obtain a second negative electrode active material layer. Therefore, compared with a self-supporting film manufactured using a typical binder including a triblock copolymer containing a first hard block and a second hard block, the self-supporting film can achieve a stronger tensile strength. Therefore, even if a low content of binder is used, for example, a lower limit of 5% by weight, a lower limit of 3% by weight, or a lower limit of 2% by weight relative to the total weight of the composition for forming the negative electrode, a self-supporting film for the negative electrode of a lithium secondary battery having excellent tensile strength can be manufactured. In addition, a self-supporting film for a negative electrode is obtained using a composite powder including a treated (e.g., pulverized) product obtained by treating (e.g., pulverizing) a self-supporting film for a negative electrode initially formed. Therefore, the dispersibility of the binder can be improved, so that the flexibility of the manufactured self-supporting film for a negative electrode and the electrode including the self-supporting film can be improved. In addition, this can improve the electrolyte stability of the manufactured lithium secondary battery.
[0070] The content of the first hard block and the second hard block may be in the range of 10 to 60%, preferably 15 to 55%, and more preferably 20 to 50%, based on the total content of the triblock copolymer. When the content of the first hard block and the second hard block satisfies the above numerical range, the bonding strength may be further improved due to its strong interaction with the negative electrode active material or the conductive material, and the triblock copolymer may have appropriate flexibility and thus may have excellent formability.
[0071] The weight average molecular weight of each of the first hard block and the second hard block may be in the range of 9,000 g / mol (inclusive) to 20,000 g / mol (inclusive), preferably 9,500 g / mol (inclusive) to 20,000 g / mol (inclusive), more preferably 10,000 g / mol (inclusive) to 20,000 g / mol (inclusive). When the weight average molecular weight of each of the first hard block and the second hard block satisfies the above numerical range, physical crosslinking force can be improved, allowing a more stable three-dimensional network to be formed, and processability can be further improved due to easy deformation in manufacturing an electrode.
[0072] Each of the first glass transition temperature and the second glass transition temperature corresponding to the first hard block and the second hard block, respectively, may be in the range of 50°C (inclusive) to 120°C (inclusive). The third glass transition temperature corresponding to the soft block may be in the range of -120°C (inclusive) to 50°C (inclusive). Preferably, each of the first glass transition temperature and the second glass transition temperature may be in the range of 80°C (inclusive) to 120°C (inclusive), and the third glass transition temperature may be in the range of -120°C (inclusive) to -80°C (inclusive). More preferably, each of the first glass transition temperature and the second glass transition temperature may be in the range of 80°C (inclusive) to 110°C (inclusive), and the third glass transition temperature may be in the range of -110°C (inclusive) to -80°C (inclusive). Since the first hard block, the second hard block and the soft block contained in the triblock copolymer have a glass transition temperature within the above numerical range, not only can a more reversible formation of a composition for forming a negative electrode of a lithium secondary battery containing a binder containing the triblock copolymer be achieved, but also the durability and flexibility of the electrode made from the above composition can be further improved and its shape can be more effectively maintained.
[0073] The soft block, the first hard block and the second hard block contained in the triblock copolymer may not affect each other and may show independent characteristics. Therefore, the soft block can independently provide flexibility to the self-supporting film for the negative electrode of the lithium secondary battery formed in the end, and the first hard block and the second hard block can independently provide strong binding force with the negative electrode active material to the self-supporting film for the negative electrode of the lithium secondary battery formed in the end. In addition, the soft block and the hard block have different glass transition temperatures. Therefore, when the self-supporting film for the negative electrode is formed (by calendering, etc.) at a temperature higher than the glass transition temperature of the hard block, the formability of the triblock copolymer becomes good. After the film is formed, the temperature immediately exposed to the glass transition temperature lower than the hard block and the glass transition temperature higher than the soft block can allow the triblock copolymer to be flexible and maintain high strength, so that the self-supporting film for the negative electrode of the lithium secondary battery including the triblock copolymer can not be easily destroyed by external stimuli.
[0074] The triblock copolymer is stable at a negative potential, so that the occurrence of side reactions is suppressed. Therefore, when the triblock copolymer is used as a binder for a negative electrode of a lithium secondary battery, the life performance of the electrode can be improved.
[0075] The negative electrode active material may include at least one selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of alloying with lithium, and a lithium-containing active material.
[0076] The carbonaceous active material may be, for example, graphite, hard carbon, soft carbon, or graphene. The graphite may be artificial graphite, natural graphite, a mixture of artificial graphite and natural graphite, natural graphite coated with artificial graphite, or a combination thereof.
[0077] The carbonaceous active material has a relatively small change in crystal structure during the insertion / extraction process of lithium ions, enabling the redox reaction at the electrode to be continuous and repetitive, thereby achieving a lithium secondary battery with high capacity and longer lifespan.
[0078] For example, the silicon-based active material may be Si, SiO m , Si-C composite, Si-Q alloy, or a combination thereof, where m is 0 < m ≤ 2, and Q is an alkali metal, alkaline earth metal, group 13 to group 16 element, transition metal, rare earth element, or a combination thereof, and Si is excluded from Q.
[0079] The metal-based active material that can be alloyed with lithium may include, for example, B, Al, Ga, In, Ge, Sn, Pb, P, As, Sb, Bi, Mg, Ca, Zn, Cd, Pd, Ag, Au, Pt, their alloys, or their oxides.
[0080] The lithium-containing active material may be, for example, lithium-containing titanium composite oxide (LTO).
[0081] The conductive material may include at least one selected from the group consisting of graphite, activated carbon, carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene, and carbon fiber.
[0082] The first film-forming process may be performed in a dry manner. That is, the composition for forming the negative electrode of the lithium secondary battery used in the first film-forming process substantially does not contain a solvent. When the first film-forming process is performed in a wet manner, there are limitations in increasing the electrode loading due to the liquid slurry, and a network structure between the binder and the active material / conductive material cannot be formed. However, according to the present disclosure, the film-forming process is performed in a dry manner, enabling a large electrode loading with high energy density, and thereby manufacturing a lithium secondary battery in which a network structure between the binder and the active material is more effectively formed.
[0083] The first film-forming process may include calendering (rolling). That is, the first negative electrode active material layer may be formed by passing a composition for forming the negative electrode of the lithium secondary battery containing a negative electrode active material, a conductive material, and a binder between a pair of rollers and rolling the composition therebetween. In this regard, the diameter of the rollers may be, for example, 50 - 1000 mm, preferably 100 - 1000 mm, more preferably 100 - 500 mm.
[0084] In addition, the calendering in the above-mentioned first film forming process can be performed at a temperature corresponding to or higher than the first glass transition temperature and the second glass transition temperature of the first hard block and the second hard block, respectively. Specifically, the calendering can be performed at 50 to 140° C., preferably 80 to 140° C., and more preferably 80 to 130° C. Therefore, the formability of the triblock copolymer including the first hard block and the second hard block and the binder including the same can be further improved.
[0085] External forces such as shear force and extension force may be applied to the composition by calendaring, thereby preparing a first self-supporting film for a negative electrode of a lithium secondary battery.
[0086] Specifically, the first negative electrode active material layer manufactured in a dry manner may be an unsupported negative electrode active material layer. An unsupported negative electrode active material layer refers to a negative electrode active material layer in the form of a thin film or a film that maintains a specific shape itself without being supported by another substrate. The unsupported negative electrode active material layer may be manufactured in this manner so that the subsequent lamination process may proceed smoothly.
[0087] Next, the first negative electrode active material layer formed in the above-mentioned first film forming step is pulverized to obtain a composite powder for forming a negative electrode.
[0088] For example, the pulverization can be carried out using a ball mill (vibration ball mill, rotary ball mill, planetary ball mill), rod mill, bead mill, disc mill, cutting mill, hammer mill, impeller mill, extruder, mixer (high-speed rotary blade type mixer, homomixer), homogenizer (high-pressure homogenizer, mechanical homogenizer, ultrasonic homogenizer), etc.
[0089] The composite powder for forming the negative electrode obtained by pulverizing the first negative electrode active material layer may have an elliptical shape, and its average sphericity may be in the range of 0.6 (inclusive) to 0.8 (inclusive), preferably 0.65 (inclusive) to 0.75 (inclusive), and more preferably 0.67 (inclusive) to 0.73 (inclusive). When the composite powder for forming the negative electrode is ellipsoidal and its average sphericity satisfies the above numerical range, the second negative electrode active material layer may be formed in the second film forming process.
[0090] The composite powder for forming the negative electrode may include particles each having an average diameter (D) in the range of 100 μm (inclusive) to 300 μm (inclusive), preferably 120 μm (inclusive) to 280 μm (inclusive), more preferably 140 μm (inclusive) to 260 μm (inclusive). 50 ) particles.
[0091] In this regard, the average diameter (D 50 ) refers to the diameter corresponding to the cumulative 50% of the cumulative volume distribution measured by a laser diffraction / scattering particle size distribution measuring device.
[0092] Finally, a second film forming process is performed using the composite powder for forming a negative electrode to form a second negative electrode active material layer.
[0093] The second film forming process can be performed in a dry manner. That is, the composite powder used in the second film forming process for forming the negative electrode does not substantially contain a solvent. Performing the second film forming process in a dry manner can allow a high electrode loading to be achieved, and a network structure between the binder and the active material or the conductive material can be formed more efficiently.
[0094] The second film forming process may include calendering (rolling). That is, the second negative electrode active material layer may be formed by passing a composite powder for forming a negative electrode between a pair of rollers and pressing and rolling the composite powder between them, the composite powder being formed by pulverizing the first negative electrode active material layer. For this, the diameter of the roller may be, for example, in the range of 50 to 1000 mm, preferably 100 to 1000 mm, and more preferably 100 to 500 mm.
[0095] In addition, the calendering in the second film forming process can be performed at a temperature above the first glass transition temperature and the second glass transition temperature corresponding to the first hard block and the second hard block, as in the above-mentioned first film forming process. Specifically, the calendering can be performed at 50 to 140° C., preferably 80 to 140° C., and more preferably 80 to 130° C. Therefore, the formability of the triblock copolymer including the first hard block and the second hard block and the binder including the same can be further improved.
[0096] The composite powder for forming the negative electrode can be subjected to a second film forming process, and the composite powder for forming the negative electrode is obtained by crushing the first negative electrode active material layer formed in the first film forming process. Therefore, compared with the self-supporting film for the negative electrode formed only by the first film forming process, the dispersibility of the binder in the self-supporting film finally formed for the negative electrode can be further improved. Therefore, a more rigid three-dimensional network structure can be formed, that is, a network structure in which a binder in a linear form (discontinuous column or line) connects the negative electrode active material or the conductive material to each other.
[0097] According to another embodiment of the present disclosure, a self-supporting film for a negative electrode of a lithium secondary battery is provided, wherein the self-supporting film includes a negative electrode active material layer, the negative electrode active material layer includes multiple domains of negative electrode active material, multiple domains of conductive material and a binder, wherein the binder comprises a triblock copolymer, the triblock copolymer having: a soft block derived from an aliphatic or alicyclic diene monomer and having a rubber phase at room temperature; and a first hard block and a second hard block respectively connected to both ends of the soft block, the first hard block and the second hard block being derived from an aromatic ring-containing ethylenically unsaturated monomer and having a glass phase at room temperature, wherein the binder has discontinuous columns connecting one domain of active material or one domain of conductive material to another domain of active material or another domain of conductive material, wherein the binder has an average width perpendicular to the length direction of the binder in the range of 10 nm (inclusive) to 150 nm (inclusive).
[0098] In addition, the same contents previously described in the method for manufacturing a self-supporting film for a negative electrode of a lithium secondary battery can be applied to the triblock copolymer containing the soft block, the first hard block, and the second hard block.
[0099] One domain of active material or one domain of conductive material and another domain of active material or another domain of conductive material may be connected to each other via a binder in the form of a discontinuous column (or line) to form a three-dimensional network. In other words, a binder in the form of a discontinuous column (or line) connects the outer surface of one domain of active material or one domain of conductive material to the outer surface of another domain of active material or the outer surface of another domain of conductive material to form a composite of a three-dimensional network structure in a network (active material or conductive material is located at the intersection and a linear binder connects them to each other). The three-dimensional network may be due to the strong π-π interaction between the first hard block and the second hard block contained in the triblock copolymer and the negative electrode active material or conductive material.
[0100] Specifically, in each of the first film forming process and the second film forming process, first, due to a high external force (shear force or extension force, etc.), contact occurs between the binder containing the triblock copolymer and the negative electrode active material or the conductive material. Then, as the external force decreases at the end of each of the first film forming process and the second film forming process, the distance between the binder and the negative electrode active material or the conductive material increases, so that while the binder containing the triblock copolymer in contact with the surface of the negative electrode active material or the conductive material remains bonded thereto, the shape of the binder can be flexibly deformed into a discontinuous column or wire form.
[0101] In addition, the triblock copolymer can be columnar under pressure at a temperature at which each of the first film forming process and the second film forming process is performed, thereby forming a three-dimensional network. As described above, the domains of the active material or the domains of the conductive material and the binder in the form of discontinuous columns can be connected to each other to form a three-dimensional network, thereby manufacturing a negative electrode of a lithium secondary battery with excellent tensile strength.
[0102] Specifically, the composite powder for forming the negative electrode can be subjected to a second film forming process, and the composite powder for forming the negative electrode can be obtained by crushing the first negative electrode active material layer formed in the first film forming process. Therefore, compared with the self-supporting film for the negative electrode formed only by the first film forming process, the dispersibility of the binder in the self-supporting film finally formed for the negative electrode can be further improved. Therefore, a more rigid three-dimensional network structure can be formed, that is, a network structure in which a linear form of binder (discontinuous columns or lines) connects the negative electrode active materials or conductive materials to each other.
[0103] The average width of the binder perpendicular to its length direction can be in the range of 10nm (inclusive) to 150nm (inclusive), preferably 50nm (inclusive) to 140nm (inclusive), more preferably 70nm (inclusive) to 120nm (inclusive) and most preferably 80nm (inclusive) to 110nm (inclusive). When the average width perpendicular to the length direction of the binder meets the above-mentioned numerical range, a dense three-dimensional network of the binder can be formed between the active material, between the conductive material or between the active material and the conductive material. Therefore, the tensile strength and flexibility of the self-supporting film for the negative electrode manufactured can be increased, and in addition, excellent electrolyte stability can be achieved.
[0104] In this regard, the average width perpendicular to the length direction of the columnar binders included in the self-supporting film can be obtained as follows: the width perpendicular to the length direction at each of both ends and the center of each of five randomly selected columnar binders along the length direction is measured using an image of the binder particles observed with a scanning electron microscope (SEM), and the average value of these measured values is defined as the average width.
[0105] The average thickness of the self-supporting film may be in the range of 30 μm to 500 μm, preferably in the range of 50 μm to 300 μm, more preferably in the range of 70 μm to 200 μm.
[0106] The tensile strength of the self-supporting film may be in the range of 1 MPa (inclusive) to 2.0 MPa (inclusive), preferably in the range of 0.7 MPa (inclusive) to 1.8 MPa (inclusive), and more preferably in the range of 1.0 MPa (inclusive) to 1.6 MPa (inclusive).
[0107] According to still another embodiment of the present disclosure, there is provided a negative electrode for a lithium secondary battery, including: a current collector; and a self-supporting film for a negative electrode for a lithium secondary battery disposed on the current collector.
[0108] When the self-supporting film for the negative electrode of the lithium secondary battery is formed by the first film forming process and the second film forming process, the self-supporting film can be placed on the collector and can be laminated. The lamination can be performed by a lamination roller, and at this point, the lamination roller can be maintained at a temperature of 80° C. to 200° C. Through the lamination process, the self-supporting film and the collector for the negative electrode of the lithium secondary battery can be combined with each other.
[0109] The current collector is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, copper, aluminum or an alloy thereof, or stainless steel having a surface treated with carbon, nickel, titanium, silver, etc. can be used as the current collector.
[0110] According to still another embodiment of the present disclosure, there is provided a lithium secondary battery including a negative electrode for a lithium secondary battery; a positive electrode for a lithium secondary battery; and an electrolyte.
[0111] The positive electrode for a lithium secondary battery may include at least one positive electrode active material selected from the group consisting of lithium, nickel, cobalt, manganese, iron, tin, silicon, aluminum, and mixtures thereof. In a specific embodiment, a positive electrode such as LiCoO 2 , LiMnO 2 , LiFeO 2 , Li(Ni 0.6 Mn 0.2 Co 0.2 ) 2 , Li(Ni 0.7 Mn 0.15 Co 0.15 ) 2 , Li(Ni 0.8 Mn 0.1 Co 0.1 ) 2 , Li(Ni 0.9 Mn 0.05 Co 0.05 ) 2 , LiNi 0.6 Co 0.2 0A 0.2 O 2 , LiNi 0.7 Co 0.2 0A 0.1 O 2 , LiNi 0.8 Co 0.15 Al 0.05 O 2, LiNi 0.85 Co 0.1 Al 0.05 O 2 , LiNi 0.88 Co 0.1 Al 0.02 O 2 , LiMn 2 O 4 , LiFePO 4 The positive electrode active material can be used for the positive electrode of a lithium secondary battery.
[0112] The electrolyte may be a liquid electrolyte or a solid electrolyte.
[0113] When the electrolyte is a liquid electrolyte, the electrolyte may include a lithium salt and a non-aqueous organic solvent.
[0114] The lithium salt may be used without limitation as long as it is commonly used in an electrolyte of a lithium secondary battery. For example, the lithium salt may include a 6 , LiBF 4 , LiSbF 6 , LiAsF 6 , LiN(C 2 F 5 SO 2 ) 2 , LiN(CF 3 SO 2 ) 2 , C.F. 3 SO 3 Li, LiC(CF 3 SO 2 ) 3 , LiC 4 BO 8 , LiTFSI, LiFSI and LiClO 4 At least one compound of the group consisting of.
[0115] The non-aqueous organic solvent may include the type of organic solvent that can be used as a non-aqueous electrolyte in the manufacture of conventional lithium secondary batteries. In this regard, its content may also be appropriately changed within a generally usable range.
[0116] Specifically, the nonaqueous organic solvent may include a common organic solvent that can be used as a nonaqueous organic solvent for lithium secondary batteries, such as a cyclic carbonate solvent, a linear carbonate solvent, an ester solvent or a ketone solvent. The common organic solvent may be used alone or as a mixture of at least two substances thereof.
[0117] The cyclic carbonate solvent may include at least one selected from the group consisting of ethylene carbonate (EC), vinylene carbonate (VC), fluoroethylene carbonate (FEC), propylene carbonate (PC), and butylene carbonate (BC).
[0118] The linear carbonate solvent may include at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), and ethyl propyl carbonate (EPC).
[0119] The ester solvent may include at least one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, δ-valerolactone, and ε-caprolactone.
[0120] Polymethyl vinyl ketone or the like can be used as the ketone solvent.
[0121] When the electrolyte is a liquid electrolyte, the lithium secondary battery may further include a separator.
[0122] The diaphragm can include one or a stack of commonly used porous polymer films, for example, porous polymer films made of polyolefin polymers (such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers), respectively. Alternatively, a typical porous nonwoven fabric, for example, a nonwoven fabric made of high melting point glass fiber or polyethylene terephthalate fiber can be used as a diaphragm. However, the present disclosure is not limited thereto. In addition, a diaphragm coated with a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength. Alternatively, the diaphragm can have a single-layer or multilayer structure.
[0123] In this regard, the pore size of the porous membrane may generally range from 0.01 to 50 μm, and its porosity may range from 5% to 95%. Furthermore, the thickness of the porous membrane may generally range from 5 to 300 μm.
[0124] In one embodiment, when the electrolyte is a solid electrolyte, the electrolyte may be a polymer-based solid electrolyte, an oxide-based solid electrolyte, a sulfide-based solid electrolyte, or a mixture thereof.
[0125] The polymer solid electrolyte may include, for example, polyether-based polymers, polycarbonate-based polymers, acrylate-based polymers, polysiloxane-based polymers, phosphazene-based polymers, polyethylene derivatives, alkylene oxide derivatives such as polyethylene oxide, phosphate polymers, poly-stirred lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride and its derivatives, polymers containing ion dissociated groups, etc. In addition, as polymer resins, polymer electrolytes may include branched copolymers, comb-like polymers, and cross-linked polymer resins, etc., in which amorphous polymers such as PMMA, polycarbonate, polysiloxane, and / or phosphazene are copolymerized with a PEO (polyethylene oxide) main chain. The polymer electrolyte may include at least one of them.
[0126] Oxide-based solid electrolytes may include, for example, LLZO-based compounds, LLTO-based compounds such as Li 3x La 2 / 3- x TiO 3 , LISICON compounds such as Li 14 Zn(GeO 4 ) 4 , LATP compounds such as Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 LAGP compounds such as (Li 1+x Ge 2-x Al x (PO 4 ) 3 ), and LIPON compounds, etc. However, the present disclosure is not particularly limited thereto.
[0127] The sulfide-based solid electrolyte may include at least one of the following: Li 6 PS 5 Cl, Li 2 SP 2 S 5 , Li 2 S-LiI-P 2 S 5 , Li 2 S-LiI-Li 2 OP 2 S 5 , Li 2 S-LiBr-P 2 S 5 , Li 2 S-Li 2 OP 2 S 5 , Li 2 SLi3 PO 4 -P 2 S 5 , Li 2 SP 2 S 5 -P 2 O 5 , Li 2 SP 2 S 5 -SiS 2 , Li 2 SP 2 S 5 -SnS、Li 2 SP 2 S 5 -Al 2 S 3 , Li 2 S-GeS 2 or Li 2 S-GeS 2 - At least one of ZnS. However, the present disclosure is not particularly limited thereto.
[0128] Hereinafter, the present disclosure is described in more detail based on examples. However, these examples are only intended to help understand the present disclosure, and the scope of the present disclosure is not limited to these examples in any way.
[0129] <Present Example 1> Production of Self-Supporting Film for Negative Electrode 1
[0130] First, graphite as a negative electrode active material, carbon as a conductive material, and SBS triblock copolymer (glass transition temperature of polystyrene block: 100°C, glass transition temperature of polybutadiene block: -100°C) as a binder were mixed with each other in a mass ratio of 96:1:3 without a solvent. The mixed powder was rolled using a double roll press heated to 120°C to produce a self-supporting film for the negative electrode.
[0131] The self-supporting film for anode formed by the above film forming process was pulverized using a pulverizer capable of applying a transfer force thereto, and the mixed powder as the pulverized product was put back into a roll press and the temperature was raised to 100° C. or higher to form a film.
[0132] <Present Example 2> Production of Self-Supporting Film for Negative Electrode 2
[0133] A self-supporting film for a negative electrode was manufactured in the same manner as in the present Example 1, except that graphite, a conductive material, and a binder were mixed with each other in a mass ratio of 97:1:2.
[0134] <Present Example 3> Preparation of Self-Supporting Film for Negative Electrode 3
[0135] A self-supporting film for a negative electrode was manufactured in the same manner as in the present Example 1, except that graphite, a conductive material, and a binder were mixed with each other in a mass ratio of 95:1:4.
[0136] <Reference Example 1> Preparation of Self-Supporting Film for Negative Electrode 4
[0137] First, graphite as a negative electrode active material, carbon as a conductive material, and SBS triblock copolymer (glass transition temperature of polystyrene block: 100°C, glass transition temperature of polybutadiene block: -100°C) as a binder were mixed with each other in a mass ratio of 96:1:3 without a solvent. The mixed powder was rolled using a double roll press heated to 120°C to produce a self-supporting film for the negative electrode.
[0138] <Reference Example 2> Preparation of Self-Supporting Film for Negative Electrode 5
[0139] A self-supporting film for a negative electrode was manufactured in the same manner as in Reference Example 1, except that graphite, a conductive material, and a binder were mixed with each other in a mass ratio of 97:1:2.
[0140] <Reference Example 3> Preparation of Self-Supporting Film for Negative Electrode 6
[0141] A self-supporting film for a negative electrode was manufactured in the same manner as in Reference Example 1, except that graphite, a conductive material, and a binder were mixed with each other at a mass ratio of 95:1:4.
[0142] <Experimental Example 1> SEM image observation of composite powder for forming negative electrode
[0143] SEM images of the mixed powder formed after the first film formation step and pulverization in Example 1 are taken and shown in FIG. Figure 3A and Figure 3B middle.
[0144] The particles of the mixed powder formed after pulverization have an elliptical shape of a composite obtained by bonding the negative electrode active material and the conductive material with a binder, an average sphericity thereof is in the range of 0.4 to 0.9, and a size thereof is in the range of 100 to 300 μm.
[0145] In one embodiment, Figure 3C The particle analysis results of the mixed powder formed after the pulverization are shown in . It can be confirmed that the composite powder in which the binder is bonded to the negative electrode active material and the conductive material to form a composite material is distributed in the range of 100 to 500 μm.
[0146] <Experimental Example 2> SEM image observation of self-supporting film for negative electrode
[0147] The SEM image of the self-supporting film for negative electrode manufactured according to this Example 1 was taken and FIG. 4A to FIG. 4C In addition, compared with the "film forming step - pulverization - film forming step" in the present embodiment 1, the SEM image of the self-supporting film for the negative electrode in the reference example 1 in which only one film forming step was performed was obtained, and FIG. 4D to FIG. 4F Shown in.
[0148] Reference Figure 4A , it can be confirmed that the thickness of the self-supporting film for the negative electrode formed through the film forming process-pulverization-film forming process is about 109 μm.
[0149] refer to Figure 4B and Figure 4C It can be determined that after the "film formation process-crushing-film formation process", the columnar SBS binder is connected and arranged between the negative electrode active materials, between the conductive materials, and between the negative electrode active materials and the conductive materials to form a network structure, and the average width of the length direction perpendicular to the columnar SBS binder is about 80 to 110 nm.
[0150] On the contrary, reference Figure 4D , it was confirmed that the thickness of the self-supporting film for a negative electrode according to Reference Example 1 formed by only one film formation step was about 105 μm.
[0151] Reference Figure 4E and Figure 4F , it was determined that when the film forming process was performed only once (reference example 1), the columnar SBS binder was connected and arranged between the negative electrode active materials, between the conductive materials, and between the negative electrode active materials and the conductive materials to form a network structure as in this example 1, and the average width perpendicular to the length direction of the columnar SBS binder was greater than about 0.4 to 0.5 μm, which was greater than the average width in this example 1.
[0152] Specifically, it can be confirmed that, in the case of the present Example 1, a large amount of columnar binders connecting the negative electrode active material and / or the conductive material to each other exist.
[0153] To summarize the above results, in the film forming process, the columnar binder is connected to and arranged between the negative electrode active materials, between the conductive materials, and between the negative electrode active materials and the conductive materials to form a network structure. If the first film forming process, the pulverizing process, and the second film forming process are performed in sequence, when a certain amount of three-dimensional network structure is formed, a denser three-dimensional network structure can be formed due to the additional film forming process.
[0154] Figure 4GThe columnar SBS binder connecting the negative electrode active materials or the conductive materials to each other in the mesh structure of the self-supporting film for the negative electrode manufactured according to each of the present Example 1 and the Reference Example 1 is schematically shown. In other words, it can be determined that the discontinuous SBS binder in the form of columnar dots contacts the outer surface of each of the active material domain and the conductive material domain, and connects the negative electrode active materials or the conductive materials to each other.
[0155] <Experimental Example 3> Measurement of electrolyte stability of self-supporting film for negative electrode
[0156] The self-supporting film for negative electrode according to each of the present Example 1 and Reference Example 1 was immersed in the electrolyte for 1 minute, and then a rubber rod was used to apply 10 impacts to the vial containing the electrolyte, and then the change in its appearance was visually observed. The results are shown in Figure 5A and Figure 5B middle.
[0157] As a result of the experiment, it can be seen that the self-supporting film for the negative electrode according to the present embodiment 1 maintained its original shape after impact was applied thereto, while the self-supporting film for the negative electrode according to the reference example 1 failed to maintain its original shape after impact was applied thereto and was therefore completely separated.
[0158] The electrolyte stability of the self-supporting film for a negative electrode according to the present Example 1 is achieved due to a more rigid three-dimensional network between the binder and the negative electrode active material or the conductive material, which is obtained by performing a film forming process, pulverization, and a subsequent additional film forming process.
[0159] <Experimental Example 4> Measurement of tensile strength and flexibility of self-supporting film for negative electrode
[0160] First, the tensile strength of the self-supporting film for the negative electrode manufactured according to each of Examples 1 to 3 and Reference Examples 1 to 3 was evaluated. The samples were prepared by punching each self-supporting film into a size of 2 cm wide and 6 cm long, and the tensile strength thereof was measured at a speed of 5 mm / min of the UTM device.
[0161] refer to Fig. 6A It can be seen that when the binder content is constant, the present embodiment 1 or embodiment 3 that performs pulverization and another film forming process has a higher tensile strength than the tensile strength of the reference example 1 or 3 that performs only one film forming process (present embodiment 1> reference example 1, present embodiment 3> reference example 3). This is because the process of "film forming process-pulverization-film forming process" allows the negative electrode active material, the conductive material, or the negative electrode active material and the conductive material to be connected to each other by the SBS binder to form a network more rigidly compared to a single film forming process.
[0162] In addition, in Reference Example 2, a film having a binder content of 2 mass % can be formed, but the tensile strength of the self-supporting film formed is too weak to measure the tensile strength. However, in the case of the present Example 2 in which the first film forming step, pulverization, and the second film forming step are performed, a film can be formed with a binder content of 2 mass %.
[0163] Next, the flexibility in each of the MD and TD directions of the self-supporting film for a negative electrode manufactured according to each of the present Example 1, the present Example 2, the Reference Example 1, and the Reference Example 2 was evaluated. The flexibility was evaluated based on whether cracks occurred when a marker pen was wrapped with each self-supporting film for a negative electrode. Figure 6B and Figure 6C : represents an experimental process for evaluating the flexibility of the self-supporting film for a negative electrode manufactured according to this Example 1 in each of the MD and TD directions.
[0164] When Example 1 is compared with Reference Example 1 having a binder content of 3 mass %, the self-supporting film for the negative electrode of Example 1 that has been subjected to a pulverization treatment is flexible in both the MD and TD directions, while the self-supporting film for the negative electrode of Reference Example 1 that has not been subjected to a pulverization treatment is flexible in the MD direction but has cracks in the TD direction.
[0165] In addition, when the present embodiment 2 is compared with the reference example 2 in which the binder content is 2 mass %, the self-supporting film for the negative electrode of the present embodiment 2 that has been subjected to the pulverization treatment is flexible in both the MD and TD directions, while the self-supporting film for the negative electrode of the reference example 2 that has not been subjected to the pulverization treatment has basically no flexibility and very weak basic tensile strength, and therefore its evaluation result is not feasible.
[0166] <Present Example 4> Manufacturing of Lithium Secondary Battery 1
[0167] The self-supporting film for a negative electrode according to the present Example 3 was placed on one surface of a copper foil coated with a primer layer, and was subjected to lamination using a laminating roll maintained at 120° C. to manufacture a negative electrode of a lithium secondary battery.
[0168] The manufactured negative electrode, lithium metal as the positive electrode, and 1M LiPF 6 , 2% by weight of vinylene carbonate (VC), and 1% by weight of LiPO 2 F 2 The electrolytes mixed with each other in a solvent in which EC:EMC:DEC were mixed with each other in a volume ratio of 5:9:6 were used to manufacture a coin type half-cell.
[0169] <Reference Example 4> Production of lithium secondary battery 2
[0170] A coin-type half cell was manufactured in the same manner as in this Example 4, except that the self-supporting film for a negative electrode according to Reference Example 1 was used instead of the self-supporting film for a negative electrode according to this Example 3.
[0171] <Experimental Example 5> Performance evaluation of lithium secondary battery
[0172] The lithium secondary batteries according to each of the present Example 4 and the Reference Example 4 were subjected to one cycle at a rate of 0.1 C, and the charge capacity and discharge capacity were measured and reported in the following Tables 1 and Figure 7 The charge capacity and discharge capacity are shown in .
[0173] It can be seen that as the cycle progresses, the capacity of the lithium secondary battery according to Example 4 remains stable, while the capacity of the lithium secondary battery according to Reference Example 4 becomes unstable. This is because the lithium secondary battery according to this Example 4 has improved tensile strength and flexibility of the electrode and improved electrolyte stability due to the negative electrode including the self-supporting film for the negative electrode formed by the film formation-crushing-film formation process.
[0174] [Table 1]
[0175]
[0176] Using the method for manufacturing a self-supporting film for a negative electrode of a lithium secondary battery according to the present disclosure, the binder can be bonded to the negative electrode active material or the conductive material via a strong interaction with the negative electrode active material or the conductive material, and thus, a self-supporting film for a negative electrode of a lithium secondary battery that is electrochemically stable even at a negative potential and has excellent tensile strength and good formability can be manufactured.
[0177] Although the present disclosure has been described above with reference to exemplary embodiments and the accompanying drawings, the present disclosure is not limited thereto but various modifications and changes may be made by those skilled in the art without departing from the spirit and scope of the present disclosure as claimed in the appended claims.
Claims
1. A method for manufacturing a self-supporting film for a negative electrode of a lithium secondary battery, the method comprising: forming a first electrode active material film using a composition comprising a negative electrode active material, a conductive material, and a binder; processing the first electrode active material film to obtain a composite powder; and Using the composite powder to form a second electrode active material film, Wherein, the binder comprises a triblock copolymer, and the triblock copolymer comprises: A soft block derived from aliphatic or alicyclic diene monomers and having a rubber phase at room temperature; and The first hard block and the second hard block are connected to both ends of the soft block, respectively. It is derived from an ethylenically unsaturated monomer containing an aromatic ring and has a glass phase at room temperature.
2. The method according to claim 1, wherein: The composite powder includes powder elements each having an ellipsoidal shape, and an average sphericity of the ellipsoidal shape is in the range of 0.6-0.
8.
3. The method according to claim 1, wherein: The composite powder comprises particles each having an average diameter (D 50 ) particles.
4. The method according to claim 1, wherein: The binder includes particles in a spherical shape, and the average sphericity of the spherical shape is in the range of 0.8-1.
0.
5. The method according to claim 1, wherein: The binder comprises particles, each of which has an average diameter (D 50 ).
6. The method according to claim 1, wherein: The first glass transition temperature and the second glass transition temperature corresponding to the first hard block and the second hard block, respectively, are both in the range of 50°C to 120°C, wherein the third glass transition temperature corresponding to the soft block is in the range of -120°C to -50°C.
7. The method according to claim 1, wherein: The soft block is derived from the aliphatic or alicyclic diene-based monomer including at least one selected from the group consisting of butadiene-based monomers, pentadiene-based monomers, and hexadiene-based monomers.
8. The method according to claim 1, wherein: The first hard block and the second hard block are each independently derived from the aromatic ring-containing ethylenically unsaturated monomer including at least one of a styrene-based monomer and an aromatic (meth)acrylic-based monomer.
9. The method according to claim 1, wherein: At least one of forming the first electrode active material film and forming the second electrode active material film includes rolling, Wherein, the calendering is performed at a temperature equal to or higher than a first glass transition temperature and a second glass transition temperature corresponding to the first hard block and the second hard block, respectively.
10. A self-supporting film suitable for a negative electrode of a lithium secondary battery, the self-supporting film comprising: a negative electrode active material layer, comprising a plurality of domains of negative electrode active material, a plurality of domains of conductive material and a binder, Wherein, the binder comprises a triblock copolymer, and the triblock copolymer has: A soft block derived from aliphatic or alicyclic diene monomers and having a rubber phase at room temperature; and The first hard block and the second hard block are connected to both ends of the soft block, respectively, are derived from an ethylenically unsaturated monomer containing an aromatic ring, and have a glass phase at room temperature, wherein the binder has discontinuous columns connecting one domain of the active material or one domain of the conductive material to another domain of the active material or another domain of the conductive material, The binder has an average width perpendicular to its length direction in a range of 10 nm to 150 nm.
11. The self-supporting film according to claim 10, wherein The domains of the active material or the domains of the conductive material are connected to each other with the binder in the form of discontinuous columns to form a three-dimensional network.
12. The self-supporting film according to claim 10, wherein An average width of the binder is in a range of 70 nm to 120 nm, wherein the average width of the binder is perpendicular to a length direction of the binder.
13. The self-supporting film according to claim 10, wherein: Each of a first glass transition temperature and a second glass transition temperature corresponding to the first hard block and the second hard block, respectively, is in a range of 50° C. to 120° C., The third glass transition temperature corresponding to the soft block is in the range of -120°C to -50°C.
14. The self-supporting film according to claim 11, wherein The soft block is derived from the aliphatic or alicyclic diene-based monomer including at least one selected from the group consisting of butadiene-based monomers, pentadiene-based monomers, and hexadiene-based monomers.
15. The self-supporting film according to claim 10, wherein: The first hard block and the second hard block are each independently derived from the aromatic ring-containing ethylenically unsaturated monomer including at least one of a styrene-based monomer and an aromatic (meth)acrylic-based monomer.
16. The self-supporting film according to claim 10, wherein The average thickness of the self-supporting film is in the range of 30 μm to 500 μm.
17. The self-supporting film according to claim 10, wherein: The tensile strength of the self-supporting film is in the range of 1.0 MPa to 2.0 MPa.
18. A negative electrode for a lithium secondary battery, comprising: Current collector; as well as The self-supporting film for the negative electrode of the lithium secondary battery is provided on the current collector, and the self-supporting film comprises the self-supporting film for the negative electrode of the lithium secondary battery according to claim 10 .
19. A lithium secondary battery comprising: The negative electrode according to claim 18; positive electrode; as well as Electrolytes.
20. A vehicle comprising the lithium secondary battery according to claim 19.
Citation Information
Patent Citations
A method of delivering customized products
KR1020230106485A